2020
DOI: 10.1002/pbc.28310
|View full text |Cite
|
Sign up to set email alerts
|

Can FDG‐PET replace biopsy for the evaluation of residual tumor in pediatric mature B‐cell non‐Hodgkin lymphoma?

Abstract: Introduction The aim of our study is to evaluate the role of 18F‐labeled fluorodeoxy glucose positron emission tomography (18FDG‐PET) scan for the detection of viable residual mass in pediatric mature B‐cell non‐Hodgkin lymphoma (NHL). This study also aims to detect the negative predictive value, positive predictive value (PPV), sensitivity, and specificity of 18FDG‐PET. Patients and methods A retrospective, cross‐sectional nonrandomized study was carried out. We included all patients with newly diagnosed matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Some researchers reported that most of lymphoma patients showed 18 F-FDG–avid lesions including the mantle cell lymphoma and follicular lymphoma 1–3 . However, we found out that in some cases it is not easy to delineate the lymphoma lesions using 18 F-FDG PET/CT 4,5 without 64 Cu-DOTA-rituximab PET/CT. 64 Cu-DOTA-rituximab PET/CT could be a powerful tool for the diagnosis and monitoring treatment response of lymphoma because of imaging the CD20 expression 6,7 .…”
mentioning
confidence: 70%
“…Some researchers reported that most of lymphoma patients showed 18 F-FDG–avid lesions including the mantle cell lymphoma and follicular lymphoma 1–3 . However, we found out that in some cases it is not easy to delineate the lymphoma lesions using 18 F-FDG PET/CT 4,5 without 64 Cu-DOTA-rituximab PET/CT. 64 Cu-DOTA-rituximab PET/CT could be a powerful tool for the diagnosis and monitoring treatment response of lymphoma because of imaging the CD20 expression 6,7 .…”
mentioning
confidence: 70%
“…[18]. Insbesondere bei asymptomatischen Kindern und Jugendlichen wird daher eine Bestätigung durch eine Biopsie empfohlen, sofern dies auch möglich ist [19]. Falsch-positive Ergebnisse wurden auf zeitnah vor der PET erfolgt Biopsien, reaktive Lymphknoten bzw.…”
Section: Therapieansprechen/restagingunclassified